HOW TO DRIVE PURCHASE DECISIONS ON TOKOPEDIA E-COMMERCE - Humairoh, Humairoh; Suprobo, Rosaldila (Dynamic Management Journal, 2024)
This study aims to analyze the influence of brand image, feature completeness, and consumer perception on purchase decisions on Tokopedia E-commerce in Tangerang Regency. This quantitative study uses a research sample of 96 respondents using Tokopedia determined by purposive sampling. Sample data collection using a questionnaire instrument. The data analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression test, and determination coefficient test using SPSS software version 25. The study results show that partial brand image (X1) has a positive and significant effect on purchase decisions (Y). The t calculation shows this> t table, namely (2.095 > t-table 1.985), the completeness of the feature (X2) has a positive and significant effect on the purchase decision (Y). This is shown by t calculation > t table (3.558 > t-table 1.985). Consumer perception (X3) has a positive and significant effect on purchase decisions (Y), shown by t calculation > t table, namely (6.869 > t-table 1.985). And simultaneously brand image (X1), feature completeness (X2), and consumer perception (X3) have a positive and significant effect on purchase decisions (Y), this is shown by Fcal > Ftable, namely (99.980 > F-table 2.70). The result of the determination test was 75.8%.